Developing Green Sustainable Entrepreneurship for Competitive Advantages through Green Management - Suseno Hendratmoko (Indonesian Journal of Business Analytics, 2023)
The research aims to unravel Green Competitive Advantage (GCA) management which has emerged as a crucial strategy in recent years for organizations seeking a competitive edge. The growing literature on GCA underscores its significance, highlighting its potential to enhance organizational sustainability and performance while also providing a competitive advantage. The adoption of green innovation and high environmental awareness has been shown to yield improved performance and a better competitive advantage. This contributes to sustainable business practices and positions the company favorably in the business landscape. Therefore, understanding the implications of GCA is essential for policymakers who need to define the best mechanism for developing green innovation. This, in turn, can help organizations achieve a competitive advantage and ensure business sustainability. The study emphasizes the importance of GCA literacy among practitioners and stakeholders. The novelty of the research results indicates that understanding encourages the selection of green changes within organizations, promoting GCA as a sustainable business framework. Summing up, GCA management not only offers a competitive edge for businesses but is also a step towards a sustainable future. Therefore, exploring the role of GCA in business management and its potential implications is of utmost importance in today's business world.